Colonial Trauma : A Study of the Psychic and Political Consequences of Colonial Pppression in Algeria - Lazali, Karima (Cambridge: Medford, 2021)
A powerful account of the subjective dimension of colonial domination
Keywords: Algerians--Mental health. . --History.; France--Colonies--Africa--Psychological aspects; Post-traumatic stress disorder--Algeria.; Psychoanalysis and colonialism; Political violence--Algeria; Algeria--Colonization--Psychological aspects